Nursing Management of Radiation Therapy - Shah (Gupta), Bimala (Journal of Nursing Education of Nepal, 2011)
In radiation therapy, mainly ionizing radiation (electromagnetic rays and particles) is used to cure cancer, as in Hodgkin's disease, thyroid carcinomas and cancer of uterine cervix. It may also be used to control malignant disease, and prophylactically to prevent leukemic infiltration to the brain or spinal cord. Clients receiving radiation therapy may have side effects like nausea/vomiting, anemia, thrombocytopenia etc. Nurses those are working in radiation therapy should manage the side effects. Clients and their families often have questions and concerns about radiation therapy safety. To answer questions and allay fears about the effects of radiation on the tumor and on the client’s normal tissues and organs, the nurses can explain the procedure for delivering radiation and describe the equipment, the duration of the procedure, the possible need for immobilizing the client during the procedure, and the absence of sensations, including pain, during the procedure. Health team members should follow the principles of time, distance and shielding to minimize exposure of personnel to radiation. Counseling is the most important aspect of managing the clients receiving radiation therapy.
Keywords: N/A